Facile surface tailoring of metal oxide nanoparticles via a two-step modification approach1. Issue 75 (19th August 2015) - Kockmann, A.; Hesselbach, J.; Zellmer, S.; Kwade, A.; Garnweitner, G.
<x xml:space="preserve">Abstract</x> We present a versatile two-step approach that allows a rational tailoring of the surface properties of metal oxide nanoparticles, showing many benefits e.g. for the realization of optimized particle–matrix interfaces in nanocomposites.